Modified Maximum Power Point Tracking on Models of a 400 Wp Wind Power Plant - Dwiana Hendrawati; Mulyono Mulyono; Wahyono Wahyono; Suwarti Suwarti; Nur Fatowil Aulia; Ariyanto Ariyanto; Brainvendra Widi Dinova (JAICT, 2022)
Many papers discuss the Maximum Power Point Tracking (MPPT) control simulation "Perturb and Observe" (P&O), while its realization and practice in control systems remains a major challenge. The purpose of this research to study experimentally by optimizing wind turbines PMSG connected to DC-DC converter (Boost) and resistive load. The proposed MPPT P&O control algorithm modification will be analyzed by comparing with the control method without MPPT P&O at various wind speeds. The 400 WP wind power generation system uses a boost converter simulated in MATLAB/Simulink to analyze the performance of the proposed control algorithm. Modified MPPT P&O control Wind Turbine system with 3 m/s – 7 m/s speed variation at 20 ohm to 60 ohm load, wind turbine power has been successfully improved by an average of 11.868% compared to Wind Turbines that are not installed MPPT P&O. Therefore, MPPT P&O is very suitable to be applied at low average wind speeds.